Varieties of Community Uncertainty and Clinical Equipoise - London, Alex John (Kennedy Institute of Ethics journal, 2023)
The judgments of conscientious and informed experts play a central role in two elements of clinical equipoise. The first, and most widely discussed, element involves ensuring that no participant in a randomized trial is allocated to a level of treatment that everyone agrees is substandard. The second, and less often discussed, element involves ensuring that trials are likely to generate social value by producing the information necessary to resolve a clinically meaningful uncertainty or disagreement about the relative merits of a set of interventions. The distribution of judgments in expert communities can take many forms, each with important implications for whether a trial satisfies one or both elements of clinical equipoise. In this article we use a graphical approach to represent three ways in which expert community uncertainty can vary: by spread, modality, and skew. Understanding these different distributions of expert judgment has three important implications: it helps to make operational the requirement of social value, it shows that some conditions for initiating studies to promote social value diverge from common assumptions about clinical equipoise, and it has important implications for how trials should be designed and monitored, and what patients should be told during informed consent.